Contribution to the Pselaphinae (Coleoptera: Staphylinidae) of Anatolia, Turkey - Bekchiev, Rostislav; Brachat, Volker; Anlas, Sinan; Ozgen, Inanc; Yagmur, Ersen Aydin; Orgel, Semih; Kostova, Rumyana (Inst Zoology, Bas, 2015)
As result of a short expedition during early spring in Western Turkey (Izmir, Aydin, Manisa and Denizli provinces), two new species, Bythinus beshkovi sp. n. and Bryaxis pumilus sp. n., have been discovered and are described here; the aedeagus and first two basal antennomeres of Bryaxis anatolicus Saulcy, 1878 are illustrated; faunistical data for 16 species are given, and photos of the habitus of the genera Namunia and Tremissus are provided for the first time.
Keywords: taxonomy; faunistics; new species; Pselaphinae; Turkey; Asia